Is Saccharomyces cerevisiae azoreductase the plasma membrane ferric reductase? - Ramalho, Patrícia A. (2004)
Poster apresentado na International Conference on Plasma Membrane Redox Systems and their Role in Biological Stress and Disease, 7, Asilomar, Califórnia, Estados Unidos da América, 14-18 Abril 2004.